Oxygen Concentration Dependence in Microwave Plasma‐Enhanced Chemical Vapor Deposition Diamond Growth in the (H, C, O, N) System. Issue 11 (5th April 2022) - Shimaoka, Takehiro; Yamada, Hideaki; Mokuno, Yoshiaki; Chayahara, Akiyoshi
Abstract : The dependence of nitrogen incorporation and crystalline quality of the nitrogen‐doped single‐crystal diamond on oxygen concentration is investigated. Nitrogen‐doped diamond is grown by microwave plasma‐enhanced chemical vapor deposition in the (H, C, O, N) system. Nitrogen concentration (N/H) and methane concentration (CH4 /H2 ) are fixed at 100 ppm and 4%, respectively. Oxygen concentration (O/C) is controlled from 12.5 to 50% (O/H = 0.25–1%). The growth rate of diamond decreases from 38 to 7 μm h −1 . The nitrogen concentration in the epitaxial layer increases with increasing oxygen concentration and starts to decrease when O/C > 25% (O/H > 0.5%). The full width at half maximum (FWHM) of the Raman peak at 1332 is 2.0–2.2 cm −1 . Introduction of oxygen affects incorporation of nitrogen into diamond. There is an optimum value of oxygen concentration to give the highest nitrogen concentration. This is attributed to the enhancement of the effective concentration of nitrogen‐related species in the gas phase and reduction of the growth rate both due to oxygen introduction. The results suggest that the (H, C, O, N) system could give higher concentration of nitrogen than that of the (H, C, N) system without degradation of the crystal quality. Abstract : The dependence of nitrogen incorporation into single‐crystal diamond on oxygen concentration is investigated. The nitrogen concentration in the epitaxial layer increases with increasing oxygen concentration and starts to decrease when O/C > 25%. This is attributed to the enhancement of N/C in the gas phase and reduction of the growth rate both due to oxygen introduction.